PERAN PBB DALAM MENANGGULANGI PERMASALAHAN HAM TERKAIT KONFLIK BERSENJATA LRA (LORD’S RESISTANCE ARMY) DI UGANDA - M. Radhina Rahman SPW (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The objective of this research is finding the role of the United Nations in the elimination of the Lord’s Resistance Army in Africa, and to help address the humanitarian crisis that occurred because of the civil conflict caused by the LRA armed forces in Uganda.The motive of the LRA and the horrid human rights abuse conducted, have led United Nations to engage on several engagements to eliminate the group. In other words, the United Nations has succeed to help address the humanitarian crisis by the help of Office of United Nations High Commissioner for Human Rights and kick the armed forces from Uganda.Challenges though are still faced, like the complication of the Security Council priorities, Office of United Nations High Commissioner for Human Rights’s tasks to help the humanitarian crisis, access towards LRA affected areas, and the limited mandate of the peacekeeping forces.Key Words: Role, Conflict, UN, OHCHR, Uganda, LRA, Humanitarian Crisis